MODELING OF THE OPERATIONAL PLANNING PROCESS OF WORKING LOCOMOTIVES AND LOCOMOTIVE CREWS - Zhukovytskyi, I. V.; Skalozub, V. V.; Vetrova, O. V.; Zinenko, O. L. (Science and Transport Progress, 2006)
In the paper the methods for construction of improved automated system of optimum management of locomotive depot operation have been offered. The described method of modeling the operative planning of work of the locomotives and locomotive brigades is based on the use of fuzzy multi-criteria models of the optimum assignment problem.